2015
DOI: 10.1158/1541-7786.mcr-14-0474
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for Asymmetric Cell Division Resulting in Proliferative Asynchronicity

Abstract: All cancers contain an admixture of rapidly and slowly proliferating cancer cells. This proliferative heterogeneity complicates the diagnosis and treatment of cancer patients because slow proliferators are hard to eradicate, can be difficult to detect, and may cause disease relapse sometimes years after apparently curative treatment. While clonal selection theory explains the presence and evolution of rapid proliferators within cancer cell populations, the circumstances and molecular details of how slow prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 11 publications
4
54
0
1
Order By: Relevance
“…Interestingly, we have also found that human cancer cell lines treated with allosteric small-molecule AKT inhibitors (e.g., Akti-1/2, MK-2206), at a sub-therapeutic dose (i.e., which only partially suppresses AKT signaling by about 80–90%), dramatically increase their fraction of AKT low , MCM2 low , H3K9me2 low , HES1 high cancer cells (6, 911). These quiescent cancer cells rapidly resume their cell cycle with inhibitor washout, consistent with a temporary rather than permanent cell cycle arrest, which is identical to spontaneously arising AKT low slow proliferators (10).…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Interestingly, we have also found that human cancer cell lines treated with allosteric small-molecule AKT inhibitors (e.g., Akti-1/2, MK-2206), at a sub-therapeutic dose (i.e., which only partially suppresses AKT signaling by about 80–90%), dramatically increase their fraction of AKT low , MCM2 low , H3K9me2 low , HES1 high cancer cells (6, 911). These quiescent cancer cells rapidly resume their cell cycle with inhibitor washout, consistent with a temporary rather than permanent cell cycle arrest, which is identical to spontaneously arising AKT low slow proliferators (10).…”
Section: Introductionmentioning
confidence: 82%
“…We recently discovered that epithelial cancer cells growing in culture occasionally divide asymmetrically by suppressing AKT signaling in one emerging “AKT low ” daughter cell (9, 10). This unusual type of cell division is triggered by an asymmetric decrease in Type I collagen-β1-integrin-FAK signaling, resulting in activation of the mTORC2 signaling complex, partial phosphorylation of AKT1 kinase, and its activation-induced degradation mediated by the E3-ubiquitin ligase TTC3 and the proteasome (9).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations